Theoretical Insights into The Interplay of Corporate ‎Governance and Intellectual Capital on Firm Performance in ‎Jordan - Almharat, Mohammad Khaled; Jing Hui , Kwan; Phuong Lan , Nguyen Thi (International Journal of Accounting and Economics Studies, 2026)
This conceptual study develops an integrated theoretical framework to examine how corporate governance (CG) and intellectual capital ‎‎(IC) interact to enhance firm performance (FP) in Jordanian industrial companies. The study focuses on internal and external governance ‎mechanisms, transparency and disclosure practices, and risk management, while positioning IC as a mediating factor linking CG to firm ‎performance. The framework emphasizes the strategic role of effective governance in fostering IC and improving financial, market, and ‎operational performance. This research examines all manufacturing firms traded on the Amman Stock Exchange during 20172022. As ‎a central component of the Jordanian economy, the ASE is closely connected to regional and international financial markets, supporting ‎investment inflows and market confidence. Although previous studies have explored CG, IC, and FP individually, limited research has ‎integrated these variables within a unified framework in developing economies. The research aims to cover this knowledge gap by ‎enhancing the literature and providing practical recommendations for regulators and corporate executives in Jordan.
Keywords: Corporate Governance; Firm Performance; ‏Jordanian Industrial Companies; Intellectual Capital